Cambridge O level islamiyat paper 1 (2058/1) skills book - Sohrwardy, K. Hameed (Karachi Bookmark S.N Enterprises, 2014)
"Cambridge O-Level Islamiyat Paper 1 (2058/1) Skills Book" is a practical guide designed to enhance students' exam techniques, helping them develop the skills needed to analyze and answer questions effectively in the Cambridge Islamiyat Paper 1.